(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Background: Oral carcinoma is the 6th most common carcinoma worldwide. The 5 year survival rate for oral carcinoma is only 50%. Patients of oral carcinoma are at high risk from secondary neoplasm. Over 90% of all primary malignant tumour of the oral cavity is squamous cell carcinoma. Aim: To find out the difference of clinical presentation and pathological aspects of oral cancer. Methods: In this cross sectional study 30 patients with carcinoma oral cavity from the department of otolaryngology and Head neck surgery, Bangabandhu Sheik Mujib medical University, Dhaka Medical College hospital and National Institute of cancer research & hospital, Mohakhali, Dhaka were included , period from march 2009 to September 2009. The patients were examined after admission into Hospital pre-operatively and in the post-operative period. The surgical specimen were sent for Histopathology. Results: Majority of the patients were at 6th decade where female outnumbered the male with male female ratio is 5:4. Out of 30 patients majority of the patients complains of soreness/ irritation and ulceration in the oral cavity followed by difficulty in mastication, foul breath, pain in the lesion, dysphagia, spitting of blood and excessive salivation. About the site of the lesion maximum patients having the lesion in buccal mucosa(30%) then anterior 2/3rd of tongue (23.33%), retromolar area (13.33%) in decreasing frequency. Conclusion: Oral carcinoma usually a disease of middle age and elderly people. Irritation or soreness is the commonest symptom. Most affected sites are buccal mucosa and anterior 2/ 3rd of tongue. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22012 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 15-19